Methods for landscape characterisation and mapping: A systematic review. (June 2018) - Simensen, Trond; Halvorsen, Rune; Erikstad, Lars
Highlights: Fifty-four contemporary landscape characterisation approaches were systematically reviewed. A major distinction between biophysical and 'holistic' approaches was confirmed. Three substantially different methodological strategies were identified. A trend towards increasing observer-independence over time was identified. Abstract: Due to the multidisciplinary nature of landscape research, many different systems and methods for landscape identification and classification exist. This paper provides a systematic review of 54 contemporary landscape characterisation approaches from all over the world, with the aim of identifying major methodological strategies. Multivariate statistical analyses revealed segregation of the approaches according to the landscape concept applied, the degree of observer independence and various other factors involved in the landscape characterisation process. Our review confirmed a major distinction between approaches rooted in the natural sciences and approaches rooted in the arts and the humanities. Three substantially different methodological approaches or strategies were identified: 1) 'holistic' landscape character assessment approaches, by which visual perception and socio-cultural aspects of the landscape are emphasised; 2) landscape characterisation methods based on a priori selection of geo-ecological and land-use-related properties of the landscape; and 3) biophysical landscape characterisation approaches which rely strongly on statistical analyses in order to identify gradients of variation in the presence and/or abundance of landscape elements and properties. Assessment of landform and the composition of natural and human landscape elements was a central part of all of the reviewed methods. A trend towards increasing observer-independence over time was identified.